2018
DOI: 10.4103/ijnmr.ijnmr_178_16
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychological wellbeing and body image in pregnant women

Abstract: Background:The aim of the present study was to determine the association between body image and psychological wellbeing during pregnancy.Materials and Methods:This descriptive correlational study was conducted on 320 pregnant women who were referred to health centers in Isfahan, Iran, during 2016 and had the inclusion criteria. They were selected by nonprobability convenient sampling. Data were gathered using standard psychological wellbeing and body image satisfaction questionnaires. The data were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 9 publications
(11 reference statements)
1
25
0
4
Order By: Relevance
“…There is increasing evidence that pregnant women worry about issues related to their body image and weight gain throughout the entire pregnancy process (Fahami, Amini-Abchuyeh, & Aghaei, 2018;Meireles, Neves, de Carvalho, & Ferreira, 2015a). It is estimated that approximately 50% of pregnant women report feeling dissatisfied with their bodies and their weight (Shloim, Hetherington, Rudolf, & Feltbower, 2015;Sui, Turnbull, & Dodd, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that pregnant women worry about issues related to their body image and weight gain throughout the entire pregnancy process (Fahami, Amini-Abchuyeh, & Aghaei, 2018;Meireles, Neves, de Carvalho, & Ferreira, 2015a). It is estimated that approximately 50% of pregnant women report feeling dissatisfied with their bodies and their weight (Shloim, Hetherington, Rudolf, & Feltbower, 2015;Sui, Turnbull, & Dodd, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kecemasan adalah salah satu emosi dalam diri manusia yang memengaruhi fungsi fisiologis dan psikologis serta tetap ada dalam diri manusia sepanjang hidup (Sulima et al, 2014). Beberapa penelitian meyakini bahwa proses kehamilan dapat mengganggu psychological wellbeing dan kesehatan mental, penyebab dasar stres, kecemasan dan depresi selama dan setelah kehamilan, kelainan emosional pada anak serta meningkatkan risiko masalah perilaku pada anak usia dini (Fahami et al, 2018). Masa kehamilan dan transisi perempuan menjadi seorang ibu adalah suatu masa perubahan fisiologis, psikologis dan sosial yang berlangsung secara cepat serta berpotensi menjadi tantangan dan ketegangan bagi perempuan (McNamara et al, 2019).…”
Section: Kecemasan Perempuan Dalam Masa Kehamilanunclassified
“…They found that pregnant women with pathology had lowered self-acceptance compared to pregnant women without pathology. Fahami et al (2018) evaluated self-acceptance as a component of psychological wellbeing among pregnant women from Iran, and these authors indicated that self-acceptance and personal growth positively predicted positive body image in this population. Psychological wellbeing has been found to create a positive cycle for body image and make the pregnancy more enjoyable and acceptable (Fahami et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, these studies relied upon self-acceptance scales that had been validated in populations of young adults outside of the perinatal period (Babieva et al, 2018;Bailey & Hailey, 1986;Dimitrovsky et al, 1998;Fahami et al, 2018;Podolska et al, 2013;Podolska et al, 2009). Yet, physical and psychological experiences of women who are pregnant or postpartum have unique facets that raise questions as to whether existing scales developed among other women are appropriate.…”
Section: Introductionmentioning
confidence: 99%